Karakterisasi Isoterm Sorpsi Air Biji Kopi dengan Model BET dan GAB - Sukrisno Widyotomo; O. Atmawinata; Hadi K. Purwadaria (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2011)
Many problems of coffee bean stability during storage and sea transportation are related to moisture content and the water activity of the beans. The moisture content of the beans is affected by temperature and relative humidity of the ambient air. Equilibrium of Moisture Content (EMC) defined as moisture content in substances was equal with moisture content in the surrounding air. EMC is a measuring rod of multiply microorganisme ability to cause destruction or degrading material during storage. The objectives of this research work were to determine water soption isotherms characterization of green coffee beans by BET and GAB models. Temperature used is 25-39 oC that usually found in storage of this commodity in tropical regions. Green beans used in this research are South Sulawesi arabika and robusta dried beans that dry process produce. The result showed that to be base on sorpsion area, water sorption isotherm regression equation by BET model showed that Robusta equilibrium moisture content on 70 % relative humidity which 32 oC and 25 oC temperature storage were 11.93 % and 11.22 % by BET model, and 12.81 % and 11.87 % by GAB model. For Arabica, 11.07 % and 11.09 % by BET model, and 11.65 % and 11.78 % by GAB model. ABSTRAKPermasalahan dalam mempertahankan mutu selama penyimpanan dan pengiriman berkaitan dengan kadar air dan aktivitas air di dalam bahan. Equilibrium of Moisture Content (EMC) didefinisikan sebagai kandungan air pada bahan yang seimbang dengan kandungan air udara sekitarnya. EMC merupakan tolok ukur kemampuan berkembangnya mikro organisme yang menyebabkan terjadinya kerusakan atau pembusukan bahan pada saat penyimpanan. Tujuan penelitian ini adalah untuk menentukan karakteristik isotermi sorpsi air biji kopi dengan menggunakan model BET dan GAB. Kondisi suhu yang digunakan adalah 25-39 oC sesuai dengan kondisi penyimpanan di daerah tropis. Biji kopi yang digunakan adalah kopi Arabika dan Robusta hasil pengolahan kering dari Sulawesi Selatan. Hasil penelitian menunjukkan bahwa berdasarkan pembagian daerah sorpsi, hasil analisis persamaan garis isotermi sorpsi model BET menunjukkan bahwa kadar air kopi Robusta yang berkeseimbangan dengan menggunakan model BET dan GAB pada kelembaban relatif 70 % pada suhu 32 oC masing-masing 11,93 % dan 11,22 %, sedangkan pada suhu 25 oC adalah 12,81 % dan 11,87 %. Untuk kopi Arabika pada suhu 32 oC masing-masing adalah 11,07 % dan 11,09 %, sedangkan pada suhu 25 oC adalah 11,65 % dan 11,78 %.